2015
DOI: 10.1371/journal.pone.0145176
|View full text |Cite
|
Sign up to set email alerts
|

Mutational Landscapes of Sequential Prostate Metastases and Matched Patient Derived Xenografts during Enzalutamide Therapy

Abstract: Developing patient derived models from individual tumors that capture the biological heterogeneity and mutation landscape in advanced prostate cancer is challenging, but essential for understanding tumor progression and delivery of personalized therapy in metastatic castrate resistant prostate cancer stage. To demonstrate the feasibility of developing patient derived xenograft models in this stage, we present a case study wherein xenografts were derived from cancer metastases in a patient progressing on androg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 35 publications
0
29
0
Order By: Relevance
“…Despite the tolerance of these substitutions, most mutations including S579D, F583D, and R586D, inactivate the receptor (18), indicating the structural and functional conservation of the DBD domain. For this reason, and given the lack of AR-DBD mutations in patients receiving therapy (36), we speculate that resistance could take longer to emerge from prolonged exposure to an AR-DBD specific compound compared to enzalutamide. In addition, co-administration with enzalutamide revealed no incompatibility with VPC-14449, suggesting that dual inhibition might pre-emptively select against resistance causing mutations in both DBD and LBD AR domains.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the tolerance of these substitutions, most mutations including S579D, F583D, and R586D, inactivate the receptor (18), indicating the structural and functional conservation of the DBD domain. For this reason, and given the lack of AR-DBD mutations in patients receiving therapy (36), we speculate that resistance could take longer to emerge from prolonged exposure to an AR-DBD specific compound compared to enzalutamide. In addition, co-administration with enzalutamide revealed no incompatibility with VPC-14449, suggesting that dual inhibition might pre-emptively select against resistance causing mutations in both DBD and LBD AR domains.…”
Section: Discussionmentioning
confidence: 99%
“…This collection of more than 200 transplantable PDX models of various low to high-grade human cancers, including 45 PCa lines, could be a powerful platform for translational cancer research. PDXs derived from sequential biopsies from prostate metastases from a single patient can also provide individual metastatic tumor expression signatures that may be helpful in predicting efficacy of drugs, and data confirms that the patient’s genomic and transcriptomic alterations are preserved in these sequential PDXs [25]. …”
Section: Prostate Cancer Metastasis: Recent Advances and Experimentalmentioning
confidence: 94%
“…In an effort to understand the mechanisms of therapy resistance, several large teams have undertaken whole-exome sequencing studies of metastatic biopsies from patients with prostate cancer, before and after drug treatments such as abiraterone or enzalutamide [38][39][40]. In addition, Kohli and colleagues established PDXs from pre-and post-enzalutamide treatments and comprehensively demonstrated that the genome and transcriptome landscapes of xenografts and the original patient tumour tissues were preserved in the PDXs with high fidelity, supporting their use in pre-clinical studies in the future [39].…”
Section: Autopsy Cases and Genome/growth Potentialmentioning
confidence: 99%